Critical Success Factors in the Implementation of the PPP Scheme in the Wosusokas SPAM Project (Wonogiri, Surakarta, Sukoharjo, and Karanganyar) - Prayuda, Jun Rifky; Firmansyah, Amrie; Andana, Rozano Fikri; Sasongko, Rossa Kurnia; Suhendra, Maman (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
Infrastructure development is one of the Indonesian government's programs in the RPJMN stage 4 for 2019–2024. The need for significant infrastructure development cannot be met with the state budget alone. Fiscal limitations narrow the space for the government to carry out infrastructure development. Therefore, to overcome these problems, one of the efforts made by the Indonesian government is to implement a PPP scheme. The Wosusokas SPAM project is a drinking water supply infrastructure project in the Wonogiri, Surakarta, Sukoharjo, and Karanganyar areas that uses a PPP scheme. This study uses the scoping review method to collect and analyze critical success factors that play a role in implementing PPP projects. Based on previous studies, implementing the Wosusokas SPAM project can pay attention to five critical success factors: the commitment of partners, the strength of consortiums, asset quality, the political environment, and the national PPP unit. By implementing the five critical success factors from the planning stage to contract execution, the Wosusokas SPAM project is hoped to be implemented more effectively and efficiently.